Mathematical models and methods for living systems : Levico Terme, Italy 2014 /: Levico Terme, Italy 2014. (2016) - Ciarletta, Pasquale; Hillen, Thomas, 1966-; Othmer, H. G (Hans G.), 1943-; Preziosi, Luigi; Trucu, Dumitru
No abstract available